Alternatives to standard algorithms – a study of three pupils during three and a half years - Hedrén, Rolf (NOMAD Nordic Studies in Mathematics Education, 2000)
In this article I will discuss a research project about the use of alternatives to the standard algorithms for the four arithmetic operations and especially the work of three girls who took part in the project. The girls were not taught any standard algorithms during their first five years at school. They were encouraged to use theirown written methods, including drawings, forall kindsof computations that theycouldnotdomentally. The three girls often worked together in a group. The girls were taught the standard algorithms during their sixth year at school. The results I got were mainly that the girls could manage to find their own methods, often on their own but sometimes with the help of peers or teachers. I also found that the methods that they used, were mostly less effective than the standard algorithms, but that they were more like those used for effective mental arithmetic and computational estimation. The girls acquired good number sense and good ability in mental computation, and they preferred their own methods, even after they had been taught the standard algorithms.